Development of an approach and principles for forming a new type of urethan containing multiblock copolymers with controllable structure of polymer chains - Makarova, M.A.; Tereshatov, V.V.; Senichev, V.Yu.; Vnutskikh, Zh.A.; Slobodinyuk, A.I.; Savchuk, A.V. (Perm Federal Research Centre Journal, 2019)
The method of obtaining multiblock-copolymers with heterogeneous alternating soft segments connected by hard urethane blocks, with a predetermined regular structure of polymer chains based on the use of «reverse» prepolymers, was developed, including its three-stage variant. It was shown that triblock-copolymers obtained by a new method exceeded the materials obtained by the traditional method. Block-copolymers with fragmentary ordering of polymer chains based on rheokinetic data were developed. It was found that the use of prepolymer mixtures enables developing polymeric materials with an optimal combination of microphase separation and interchain interaction in the soft phase. This part of the work was performed using compositions based on oligoethers. Such optimization enables to achieve a significant increase in the strength properties of block-copolymers. Directions for optimizing the structure and properties of polyurethane ureas with heterogeneous segments were proposed. Recommendations for the creation of block-copolymers with an improved complex of thermal, thermomechanical, and mechanical properties were developed in the direction of using polyurethanes and polyurethane ureas based on oligoethers with tetramethylene oxide units.